3.122. Rozwiąż równanie: a) ((x – 2)(2 – x))/2 – (x ^ 2 – 3x)/4 = – 2 + 3x – x ^ 2 1 ((3 – x)(x + 3))/3 – ((x + 2) ^ 2 – 4)/6 = (5 1/3 – x)/2; ((2x – 3)(x + 1))/5 – ((x – 1)(x + 1))/2 = x + 3; ((3x – 1) ^ 2 – 4)/3 – 10/3 * x ^ 2 – (5 + (2 – x)(x + 2))/2 = – x – 7 d ) b) c)

3.122. Rozwiąż równanie: a) ((x – 2)(2 – x))/2 – (x ^ 2 – 3x)/4 = – 2 + 3x – x ^ 2 1 ((3 – x)(x + 3))/3 – ((x + 2) ^ 2 – 4)/6 = (5 1/3 – x)/2; ((2x – 3)(x + 1))/5 – ((x – 1)(x + 1))/2 = x + 3; ((3x – 1) ^ 2 – 4)/3 – 10/3 * x ^ 2 – (5 + (2 – x)(x + 2))/2 = – x – 7 d ) b) c)